INFLUENCE OF FEEDING CANOLA MEAL ON THE MILK PRODUCTIVITY OF MILK COWS - Бучковська, Віта; Євстафієва, Юлія (SWorldJournal, 2024)
To date, the issue of growing rapeseed for the production of biodiesel has already been raised in Ukraine. In such conditions, a large number of rapeseed processing products, in particular meal, will soon appear on the market, which raises the question of